Social emotional competence of adolescents with Filipino migrants parents - Samarita, Rollylan V.; Capungcol Eliza Juliennes D.
This study used explanatory sequential methods to expound on the social emotional competence of adolescents with Filipino migrant parents and to describe their lived experiences, challenges, and strategies employed. A total of 120 respondents accomplished a valid and reliable questionnaire designed by Zhou and Ee (2012); among the 120 respondents, 10 adolescents with Filipino migrant parents were chosen through simple random sampling for one-on-one, in-depth interviews. Results show that adolescents with Filipino migrant parents have a moderate level of social emotional competence (SEC) (M=96.91), which is somehow similar to the other adolescents who took this survey, with Self-Awareness being most acquired competency (M=4.13), followed by Responsible Decision-Making (M=4.11) , Relationship Skills (M=3.93), Social Awareness (M=3.72), and Self-Management (M=3.47). Data further showed that the gender of the migrant parent have influences on their level of SEC, revealing that adolescents with both migrant parents have slightly lower mean scores than those with only either migrant father or mother. Moreover, a higher SEC score is obtained as the number of years working abroad increases. On the other hand, the interview responses revealed various themes in their experiences, challenges, and strategies, complementing the quantitative results. Although the experiences of these adolescents were found to be distinct and not causal to the other two, there is a compelling link found between the encountered challenges and employed strategies in the adolescents’ pursuit of managing their SEC, indicating that their experiences are not entirely negative.